IL-6 and CD4+/CD8+ are Important Indicators for Predicting Prognosis in Elderly AECOPD Patients: A Retrospective Study - Liu Q; Wang Y; Cao X; Zhang S; Xie J (Journal of Inflammation Research)
Qingqing Liu,1,2,* Yanhui Wang,1,2,* Xueshuai Cao,1,2 Shan Zhang,1,2 Juan Xie1,2 1Department of General Medicine, Shanghai Fifth People’s Hospital, Fudan University, Shanghai, People’s Republic of China; 2Center of Community-Based Health Research, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juan Xie, Email abclux@126.comPurpose: Evaluating the role of IL-6 and CD4+/CD8+ in predicting the prognosis of elderly patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD).Patients and Methods: This study retrospectively enrolled 413 elderly patients who were hospitalized for AECOPD between January 2019 and December 2021. Patients were divided into event and non-event groups based on whether they were readmitted or died due to AECOPD during 18 months of follow-up. The associations between IL-6 and CD4+/CD8+ with adverse events were assessed using Cox proportional hazards regression models, Kaplan–Meier survival analysis, and restricted cubic spline (RCS) models. Additionally, subgroup analyses were conducted to evaluate the stability of these associations, and ROC curves were used to assess the predictive ability of IL-6 combined with CD4+/CD8+ for adverse events.Results: A total of 413 patients were included in the study, with 218 experiencing adverse events. Patients with high levels of IL-6 and low levels of CD4+/CD8+ had a higher risk of adverse events. There was a non-linear relationship between IL-6 and CD4+/CD8+ with adverse events (p< 0.05). Subgroup analyses further confirmed the robustness of this association. ROC curve analysis indicated that combining IL-6 with CD4+/CD8+ significantly improved the predictive value for adverse events.Conclusion: There is a non-linear relationship between IL-6 and CD4+/CD8+ and adverse events in elderly patients with AECOPD. Combining IL-6 with CD4+/CD8+ ratios significantly enhances the predictive value for adverse events.Keywords: elderly, acute exacerbation of chronic obstructive pulmonary disease, IL-6, CD4+/CD8+, prognosis